Comparative Evaluation of Canal Centering Ability and Transportation of MiniKUT and TruNatomy Rotary File Systems in Curved Root Canals: A Cone-Beam Computed Tomographic Study - Chourasia, Hemant R.; Tarrosh, Mohammed Y.; Alfaifi, Amani; Alhazmi, Kawther; Khormi, Fatima; Jabali, Ahmad H. (European Journal of Dentistry, 2025)
The current in vitro analysis was designed to compare the centering ability and transportation of MiniKUT and TruNatomy files on the curved mesiobuccal root of the mandibular first molars using cone-beam computed tomography (CBCT).Thirty extracted mandibular first molars were randomly divided into two groups. In the first group, root canal instrumentation was performed by MiniKUT, and in the second group, TruNatomy rotary files were used. CBCT analysis of pre- and post-instrumented teeth was performed to check the canal transportation and centering ability at distances of 3, 6, and 9 mm from the root apex with the help of a prevalidated formula.Descriptive statistics were performed to calculate the mean and standard deviation. One-way ANOVA followed by post hoc Bonferroni correction was used to check the association at different levels. Pearson's correlation analysis was performed to assess the relationship between the groups.A significant association was reported with centering ability at 3, 6, and 9 mm (p = 0.001) across the groups. However, no significant association was reported with canal transportation at 3, 6, and 9 mm (p = 0.16) among both groups. TruNatomy showed higher transportation as compared to MiniKUT at 3 mm from the apex. Overall, the result suggests both files are safer to use in curved mandibular canals.Both MiniKUT and TruNatomy files demonstrated minimal root canal transportation and maintained canal shape at 3, 6, and 9 mm from the apex. These characteristics suggest that both systems are safe and effective for the instrumentation of curved mandibular canals.
Keywords: centering ability; curved canal; cone-beam computed tomography; MiniKUT; root canal transportation; TruNatomy